More Than Skin–Creating Total Facade Designs. - Arsenault, Peter J. (Architectural Record, 2022)
The public view of buildings is their facade, so it is natural to focus on the appearance or the visible skin. Louver frame depth, component profiles, louver blade spacing, and louver blade angle all play a role in determining the louver free area. Extruded aluminum trim can be provided in sizes and styles that work with multiple panels enabling architects to vary the material choices within their facade designs while keeping details that will have a similar language. BUILDING EXPANSION JOINTS The facades on larger buildings typically require intentional expansion joints (gaps) in the structure to allow for the movement of different parts of the building.